Camptotarsopoda annulitarsis Stein: redescription, description of terminalia and new record to South Africa (Diptera: Muscidae) - Couri, Márcia Souto (Zootaxa, 2014)
Camptotarsopoda Strand (Diptera, Muscidae) comprises five species restricted to the Afrotropical region. The genus belongs to the subfamily Coenosiinae and tribe Limnophorini. The type-species, C. annulitarsis (Stein), is redescribed and the male and female terminalia are described and illustrated for the first time. The species is newly recorded from South Africa. The systematic placement of the genus is confirmed among the basal Limnophorini.